Effects of a monocomponent protease from Bacillus licheniformis on broiler performance, digestibility, and carcass yield - André Luís Machado Carneiro; Marcos Barcellos Café; Fabyola Barros de Carvalho; Helder Freitas de Oliveira; Deborah Pereira Carvalho; Genilson Bezerra de Carvalho; Larissa Paula Silva Gomides; José Henrique Stringhini (Acta Scientiarum. Animal Sciences, 2022)
Two experiments were carried out to evaluate the effects of protease addition to the diet of broilers at a higher level (1× or 2×) than the nutritional value proposed for the enzyme. The first experiment, 1280 day-old chicks (Cobb500®) were randomly allocated (randomized block design, 2×2+1 factorial arrangement), five treatments, eight replicates containing 32 birds/replicate. Treatments consisted: control diet without protease (CD); CD + 1× nutritional value of the enzyme (CDM1); CD + 2× nutritional value of the enzyme (CDM2); CDM1 + protease; and CDM2 + protease. The experimental period was 42 days. The mean weight (AFW), feed intake (FI), weight gain (WG), feed conversion, and carcass yield were evaluated. Significant differences were observed for AFW, WG, FI, abdominal fat yield, and feet percentage in the carcass. In the second experiment, 120 Cobb500® chicks at 14 days of age were allotted in a completely randomized design, 2×2+1 factorial arrangement, five treatments, six replicates with four birds/replicate. The treatments were consistent with the first experiment. Significant improvements in the nitrogen balance were observed for the broilers that received protease. The use of the enzyme tested is recommended with the recommended nutritional matrix, improving the zootechnical indices of broilers.